Síndrome metabólico e actividade física. - Sofia Pereira; Duarte Pereira (Acta Médica Portuguesa, 2011)
Because the metabolic syndrome (MS) poses a growing public health problem, it is crucial to identify related modifiable risk factors. The MS is a multifaceted syndrome, however, physical activity (PA) is thought to be one of the protective factors in MS occurrence. The purpose of this study is to analyse recent literature on the association between PA and MS. Studies seem to agree in the protective effect of PA in MS occurrence, but associations are only seen in moderate or high PA levels. Differences observed in studies are probably related to different study methods. According to recent literature adequate PA levels can help to lower the risk of developing MS; PA can decrease body weight, visceral fat accumulation, improve insulin sensitivity, decrease plasma level of triglycerides, increase plasma levels of HDL cholesterol and decrease blood pressure.